The Importance of Group Work in Improving the Effectiveness of Practice-and Theory-Based Biology Classes - Asrorova Odinaoy Otabek qizi (American Journal of Biology and Natural Sciences, 2024)
: the purpose of this study is to assess the effectiveness of Applied Learning in the context of collaboration (group work) between students on a topic based on biotechnology.